Comparison of Lithuanian, Italian and British Social Business Models - Zaneta Simanaviciene; Virgilijus Dirma; Larisa Kapranova; Dominyka Beniusyte; Arturas Simanavicius (Montenegrin Journal of Economics)
Daily life in the world is accompanied by a variety of global social problems such as discrimination, ignorance, suicides, poverty, hunger, environmental pollution and several others frequently caused by human beings. These have been particularly exacerbated by the recent and arguably ongoing economic crisis. Traditional global market makers and participants are gradually getting involved in the creation of social welfare while acting in a socially responsible manner, however, such actions are often led by a certain “fashion” or public pressure. Social entrepreneurship is cited as one of those alternatives. This business model is driven by the desire to have social impact, it is one of the main tools being used as a response to fight against growing social exclusion and unemployment, dealing with sensitive regional problems. According to European Commission, one of four start-ups each year is a social business company. It is being championed as a new opportunity to reduce inequality and exclusion so as to encourage economic growth. However, although social entrepreneurship has won the attention of scientists, its inconsistent theoretical basis and very limited perception are widely argued. It is claimed that poor perception of the social business model is a major barrier to the development of such entrepreneurship in Europe.